Engaging Fathers In Care Work: A Study Exploring The Pathway Of Preventing Violence Against Women And Children In Rural Bangladesh - Islam, Afsana; Chowdhury, Umme Shefa (2016)
For healthy development of child parents’ support and care is essential. It is expected that children with an involved loving father have much more healthy childhood and self-esteem. Engaging fathers in care work and child rearing is mean to improve family cohesion and well-being. This research deals with the traditional fact of household burden and familial hierarchy among family members and of course which ultimately leads to domestic violence against women and children. Hence this paper intends to understand whether involving fathers in Care work can result in prevention of violence against women and children. To engage fathers in care work at the household level and using the qualitative method of data collection the research tries to evaluate a community dialogue session involving couples from the rural community organized by CMMS and Promundo US in the Northern Bangladesh. Engaging father results in behavioral and cognitive attachment with partner and children in a family. The evidences from a study become the popular rationales for working with fathers. The project specifically for fathers and sessions for community peoples helped to build healthy relationship among families. The paper concludes with the notion that fathers involve in the care giving work in household domain by showing the challenge against traditional ideology of fatherhood and resist the vibes of violence against women and children in family.